2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28749
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Experience Meets Graduate Academic Research: How Intersections Guide the Work of Returning Engineering Ph.D. Students

Abstract: Her research focuses on strategies for design innovations through divergent and convergent thinking as well as through deep needs and community assessments using design ethnography, and translating those strategies to design tools and education. She teaches design and entrepreneurship courses at the undergraduate and graduate levels, focusing on front-end design processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…This initial study found that the primary value driving returners back to school was utility value, with a lesser emphasis on interest and attainment, and examined the various costs and cost mitigation strategies that returners experience and utilize. Further work, utilizing EVT, was conducted in a nationwide study of engineering returners in doctoral programs [6][7][8][9][10][11][12][13]. This work found similar results for cost categories, compared to earlier work, and provided more insight into the needs of returners in these programs.…”
Section: Returnersmentioning
confidence: 87%
“…This initial study found that the primary value driving returners back to school was utility value, with a lesser emphasis on interest and attainment, and examined the various costs and cost mitigation strategies that returners experience and utilize. Further work, utilizing EVT, was conducted in a nationwide study of engineering returners in doctoral programs [6][7][8][9][10][11][12][13]. This work found similar results for cost categories, compared to earlier work, and provided more insight into the needs of returners in these programs.…”
Section: Returnersmentioning
confidence: 87%